Lithium manganese iron phosphate composite material and preparation method thereof, and lithium ion battery containing the same

By preparing a composite material with a core of lithium manganese iron phosphate and a coating of lithium iron phosphate, the problems of poor rate performance and low discharge specific capacity in electrochemical reactions are solved, and the electrochemical cycle performance of the material and the improvement of battery energy density are achieved.

CN119118094BActive Publication Date: 2025-04-29SHANGHAI LIANGFU NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411621051.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-04-29
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Lithium manganese ferrophosphate material has a ginger-Taylor effect during the electrochemical reaction, resulting in poor material rate performance, low discharge specific capacity, and poor cycle performance.

Method used

By preparing lithium manganese iron phosphate composite materials, a specific preparation method, including the selection and treatment steps of reactants, is used to form a composite material with a lithium manganese iron phosphate core and lithium iron phosphate coating, and improve the electrochemical cycling performance of the material.

Benefits of technology

It effectively improves the ginger-Taylor effect of lithium manganese iron phosphate material, improves the electrochemical cycling performance of the material, and enhances the energy density and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118094B_ABST
    Figure CN119118094B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium iron manganese phosphate composite material and a preparation method thereof, and a lithium ion battery containing the same. The preparation method is: grinding a mixture including the lithium iron manganese phosphate, the lithium iron phosphate precursor and water, sintering and crushing to form the lithium iron manganese phosphate composite material; the sintering temperature is 650°C to 750°C; wherein the lithium iron manganese phosphate forms the core of the lithium iron manganese phosphate composite material, and the average particle size of the core is 600nm-1200nm; the lithium iron phosphate precursor forms the lithium iron phosphate coating layer and the carbon coating layer of the lithium iron manganese phosphate composite material. The lithium iron manganese phosphate composite material provided by the present invention can effectively improve the Jan-Taylor effect of lithium iron manganese phosphate, and at the same time improve the electrochemical cycle performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a manganese iron lithium phosphate composite material and a preparation method thereof, and a lithium ion battery containing the composite material. Background Art

[0002] The working voltage of LiMnPO4 to Li is 4.1V. If LiMnPO4 can obtain a specific capacity equivalent to that of LiFePO4, it means that the energy density will be 35% higher than that of LiFePO4. x Fe (1-x) PO4) positive electrode material has the stability of lithium iron phosphate and can improve the energy density of the battery.

[0003] At present, there are some problems in the development of lithium manganese iron phosphate materials. First, the conductivity of lithium manganese iron phosphate is worse than that of lithium iron phosphate. Secondly, during the electrochemical reaction, the Jan-Taylor effect leads to poor rate performance of the material and low discharge specific capacity. The current means to solve the above technical problems are mainly to improve the ion and electron transmission capabilities, and at the same time introduce other metal elements to change the crystal structure of lithium manganese iron phosphate, thereby improving its stability. The improvement of electron and ion transmission can be achieved by reducing the particle size, coating and doping. At the same time, by doping other elements, the crystal form of lithium manganese iron phosphate can be improved, the Jan-Taylor effect can be alleviated, and its stability can be improved.

[0004] Carbon coating and metal ion doping methods are more common in the existing technology, but this method has limited effect in improving the Jan-Taylor effect, and still cannot give full play to the advantages of the high energy density of lithium manganese iron phosphate, and the cycle performance is poor. Summary of the invention

[0005] The present invention is mainly to overcome the defects of the prior art lithium iron manganese phosphate material, such as poor material rate performance, low discharge specific capacity and poor cycle performance, caused by the Jan-Taylor effect, and to provide a lithium iron manganese phosphate composite material and a preparation method thereof, as well as a lithium ion battery containing the same. The lithium iron manganese phosphate composite material provided by the present invention can effectively improve the Jan-Taylor effect of lithium iron manganese phosphate and improve the electrochemical cycle performance of the material.

[0006] In order to overcome the above-mentioned defects, the present invention provides the following technical solutions.

[0007] The present invention provides a method for preparing a lithium iron manganese phosphate composite material, which comprises the following steps:

[0008] (1) Preparation of lithium iron manganese phosphate: reacting reactant I with reactant II to obtain a ferromanganese phosphate precursor; reactant I includes an iron source, a manganese source and water; reactant II includes a phosphorus source, a first organic acid and water; then reacting the ferromanganese phosphate precursor with reactant III to obtain a lithium iron manganese phosphate precursor, and then grinding, sintering and crushing are performed in sequence to obtain the lithium iron manganese phosphate; reactant III includes a lithium source and water; the sintering temperature is 300°C to 680°C;

[0009] (2) Preparation of lithium iron phosphate precursor: reacting a mixture of an iron source and a phosphoric acid solution, and grinding the mixture after the reaction to obtain product A; reacting a mixture of an organic acid solution, a lithium source and a carbon source, and obtaining product B after the reaction; the order of preparing the product A and the product B is not limited; grinding the mixture of the product A and the product B to obtain a lithium iron phosphate precursor;

[0010] (3) grinding, sintering and crushing a mixture including the lithium iron phosphate, the lithium iron phosphate precursor and water to form the lithium iron phosphate composite material; the sintering temperature is 650° C. to 750° C.;

[0011] The lithium iron phosphate forms the inner core of the lithium iron phosphate composite material, and the average particle size of the inner core is 600nm-1200nm; the lithium iron phosphate precursor forms the lithium iron phosphate coating layer and the carbon coating layer of the lithium iron phosphate composite material.

[0012] In the present invention, the molar ratio of the manganese element, the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor may be (1-x): x: y, wherein (1-x): (x+y) = (5~9): (5~1).

[0013] In some specific embodiments, the molar ratio of manganese element to iron element in the lithium manganese iron phosphate composite material is 5:5, which can be achieved by any one of the following schemes a-e:

[0014] a. The molar ratio of the manganese element, the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor is 6:4:2.

[0015] b. The molar ratio of the manganese element, the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor is 7:3:4.

[0016] c. The molar ratio of the manganese element, the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor is 8:2:6.

[0017] d. The molar ratio of the manganese element, the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor is 9:1:8.

[0018] e. The molar ratio of the manganese element, the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor is 10:0:10.

[0019] The lithium manganese iron phosphate ratio of the final product is designed by the above method, but not limited to the above method.

[0020] In some specific embodiments, the molar ratio of manganese to iron in the lithium manganese iron phosphate composite material is 6:4, and the molar ratio of manganese to iron in the lithium manganese iron phosphate and the iron in the lithium iron phosphate precursor is 7:3:1.7.

[0021] In some specific embodiments, the molar ratio of manganese to iron in the lithium manganese iron phosphate composite material is 9:1, and the molar ratio of manganese to iron in the lithium manganese iron phosphate and the iron in the lithium iron phosphate precursor is 9.5:0.5:0.6.

[0022] In step (1), the iron source may be at least one of iron powder, ferroferric oxide, ferric oxide and iron oxide, preferably iron powder.

[0023] Wherein, the purity of the iron powder is preferably greater than 97wt%.

[0024] The iron powder is preferably one or more of primary reduced iron powder, secondary reduced iron powder, carbonyl iron powder, electrolytic iron powder and water atomized iron powder, more preferably water atomized iron powder, and the water atomized iron powder is spherical or ellipsoidal in shape.

[0025] The particle size of the iron powder is preferably 100-600 mesh, for example 250 mesh. The iron powder with this particle size can ensure a more complete reaction, thereby reducing the magnetic material.

[0026] In step (1), the manganese source can be at least one of manganese powder, dimanganese trioxide, trimanganese tetroxide, manganese oxide, and manganese carbonate.

[0027] Wherein, the purity of the manganese powder is preferably greater than 95wt%.

[0028] The manganese powder is preferably one or more of primary reduced manganese powder, secondary reduced ferromanganese powder, carbonyl manganese powder, electrolytic manganese powder and water atomized manganese powder, more preferably water atomized manganese powder, and the water atomized manganese powder is spherical or ellipsoidal in shape.

[0029] The particle size of the manganese powder is preferably 60-400 mesh, for example 200 mesh. Manganese powder with this particle size can ensure a more complete reaction and is conducive to forming a more uniform solid solution.

[0030] In step (1), the manganese source and the iron source may be added in the form of ferromanganese alloy.

[0031] The ferromanganese alloy is preferably prepared by water atomization.

[0032] The ferromanganese alloy is preferably spherical or ellipsoidal, and the particle size is preferably 100-300 meshes, such as 200 meshes. The ferromanganese alloy with this particle size can ensure a more complete reaction, and because the alloy reaches molecular-level fusion, it is conducive to forming a more uniform ferromanganese solid solution.

[0033] In step (1), the phosphorus source may be phosphoric acid, and the phosphoric acid is preferably food grade phosphoric acid, electrical grade phosphoric acid or industrial grade phosphoric acid; the phosphoric acid is preferably added in the form of a phosphoric acid solution, and the concentration of phosphoric acid in the phosphoric acid solution is greater than 40%, such as 85% or 62%.

[0034] In step (1), the molar ratio of the iron element provided by the iron source to the phosphorus element provided by the phosphorus source may be (0.35-0.15):1, for example, 0.3:1 or 0.4:1.

[0035] In step (1), the molar ratio of the manganese element provided by the manganese source to the phosphorus element provided by the phosphorus source may be (0.4-1.0):1, for example, 0.6:1 or 0.7:1.

[0036] In step (1), the first organic acid may be at least one of a monocarboxylic acid, a dicarboxylic acid and a tricarboxylic acid. Preferably, the first organic acid is added in the form of a solution, and the concentration of the solution is 15 wt % to 50 wt %; preferably, the amount of the first organic acid added is 15 wt % to 60 wt %, for example 24 wt %, where the percentage is the mass of the first organic acid to the mass of the phosphoric acid.

[0037] When the first organic acid is a monocarboxylic acid, the monocarboxylic acid may be one or more of acetic acid, propionic acid, lactic acid and benzoic acid.

[0038] When the first organic acid is a dicarboxylic acid, the dicarboxylic acid is one or more of oxalic acid, benzoic acid, maleic acid, adipic acid, azelaic acid, isophthalic acid, terephthalic acid and malic acid.

[0039] When the first organic acid is a tricarboxylic acid, the tricarboxylic acid is one or more of trimesic acid, trimellitic acid, citric acid and tartaric acid.

[0040] The molar ratio of the carboxyl group provided by the first organic acid to the phosphorus element provided by the phosphorus source is preferably (0.75-2.0):1, for example 0.78:1.

[0041] In some specific embodiments, the first organic acid is a monocarboxylic acid. Since there is only one carboxyl group in one organic acid molecule, the probability of gelation of the iron phosphate or manganese phosphate compound will not be increased due to the carboxyl group acting as a bridge, which is conducive to the reaction.

[0042] In some embodiments, the first organic acid is malic acid.

[0043] In step (1), a first organic acid may be added to at least one of the reactant II and the reactant III.

[0044] In step (1), at least one of the reactants I and III may further include a first dopant, wherein the first dopant includes at least one of magnesium, cobalt, titanium, vanadium, nickel, niobium, copper and tungsten; the first dopant is preferably one or more of magnesium oxide, titanium dioxide and niobium dioxide; the molar ratio of the doping element provided by the first dopant to the phosphorus element provided by the phosphorus source is preferably (0.01-0.05):1, for example, 0.03:1, 0.0145:1 or 0.02:1.

[0045] In some specific embodiments, the first dopant is titanium dioxide and magnesium oxide, wherein the molar ratio of titanium element in titanium dioxide to phosphorus element provided by phosphoric acid is 0.0145:1, and the molar ratio of magnesium element in magnesium oxide to phosphorus element provided by phosphoric acid is 0.02:1.

[0046] In step (1), the solid content of the reactant I may be 40 wt% to 80 wt%, for example 65 wt%.

[0047] In step (1), the first reaction can be carried out by dropwise adding the reactant I into the reactant II; the dropwise addition time is preferably 8 to 15 minutes, for example 10 minutes.

[0048] In step (1), the first reaction can be carried out under stirring conditions, and the stirring speed is preferably 300-800 rpm, such as 500 rpm.

[0049] In step (1), the first reaction can be carried out under an inert atmosphere. The gas of the inert atmosphere is preferably nitrogen. The flow rate of the nitrogen is preferably 15 L / min to 30 L / min, for example, 15 L / min.

[0050] In step (1), the temperature of the first reaction may be 80°C to 95°C, for example 85°C.

[0051] In step (1), the first reaction time may be 2 h to 7 h, for example 5.5 h.

[0052] In step (1), the ferromanganese phosphate precursor obtained by the first reaction is an amorphous phase material or a low-crystallinity material, which is a mixture of various ferric phosphate salts and manganese phosphate salts.

[0053] In step (1), the lithium source may be at least one of lithium carbonate and lithium hydroxide; preferably, lithium carbonate.

[0054] In step (1), the molar ratio of the lithium element provided by the lithium source to the phosphorus element provided by the phosphorus source is preferably (1.01-1.05):1, for example, 1.04:1.

[0055] In step (1), the solid content of the reactant III may be 15 wt% to 40 wt%, for example, 20 wt%;

[0056] In step (1), the reactant III may further include a reducing substance, and the reducing substance is preferably one or more of a carbon material and a conductive polymer;

[0057] When the reducing substance is a carbon material, the carbon material may be glucose, a glucose derivative, a carboxylic acid, a carboxylic acid derivative, a phenolic resin, polyethylene, polyethylene glycol, polyvinyl alcohol, a polyvinyl alcohol derivative, polyacrylic acid, a polyacrylic acid derivative, a heterocyclic polymer or a condensation polymer with N or O elements; the glucose derivative preferably includes at least one of glucose, sucrose, starch and cyclodextrin; the carboxylic acid preferably includes at least one of formic acid, acetic acid, oxalic acid, citric acid, tartaric acid and malic acid; the polyacrylic acid derivative preferably includes polyacrylate; the heterocyclic polymer with N or O elements preferably includes polyvinyl pyrrolidone.

[0058] When the reducing substance is a conductive polymer, the conductive polymer includes one or more of polyaniline, polystyrene thiol, polyacetylene, lithium carbonate and polycarbonate.

[0059] In step (1), the average particle size of the lithium manganese iron phosphate precursor may be 600 nm to 1600 nm, for example, 1400 nm.

[0060] In step (1), the lithium manganese iron phosphate precursor can participate in the subsequent reaction in the form of a solution. In the solution, the solid content of the lithium manganese iron phosphate precursor is preferably 30% to 70%, such as 44%, 45% or 46%.

[0061] The pH of the solution is preferably 3-8, such as 5.87, 5.94, 5.99 or 6.01.

[0062] The viscosity of the solution is preferably 1000 mPa·s to 20000 mPa·s, for example 8000 mPa·s, 7600 mPa·s, 12000 mPa·s, 9050 mPa·s, 10050 mPa·s, 8900 mPa·s, 7200 mPa·s, 8600 mPa·s or 9700.

[0063] In step (1), before sintering, the lithium iron manganese phosphate precursor can generally be dried, wherein the drying method is preferably spray drying. The temperature parameters of the spray drying are preferably: air inlet temperature: 220°C, outlet temperature: 110°C.

[0064] In step (1), the sintering temperature is preferably 400°C to 500°C.

[0065] In some specific embodiments, in step (1), the sintering temperature is 300°C, 450°C or 680°C.

[0066] In step (1), the sintering time may be 5 h to 20 h, for example 5 h.

[0067] In step (1), the heating rate of the sintering may be 3-10°C / min, for example 5°C / min.

[0068] In step (1), the crushing method can be air flow crushing.

[0069] In step (1), the average particle size of the lithium manganese iron phosphate may be 700 nm to 1000 nm, for example, 800 nm.

[0070] In step (1), the sintering can be carried out in a reducing gas, and the reducing gas is preferably a mixed gas of nitrogen and hydrogen or a mixed gas of argon and hydrogen; the hydrogen content of the reducing gas is 20%.

[0071] In step (2), the iron source and the phosphoric acid solution are mixed and reacted. Those skilled in the art know that the reaction is generally carried out until no gas is generated.

[0072] In step (2), the reaction is carried out under stirring, and the stirring speed is preferably 25-50 Hz, for example 30 Hz. The stirring speed will affect the formation of precipitates, thereby affecting the particle size distribution.

[0073] In step (2), the iron source is known to those skilled in the art. The present invention is a process for preparing lithium iron phosphate after the step of preparing iron phosphate. Therefore, those skilled in the art know that the iron source here does not include iron phosphate.

[0074] In step (2), the iron source is a compound containing iron and oxygen, preferably one or more of iron powder, ferric oxide, ferrosoferric oxide and ferric nitrate, and more preferably one or more of iron powder, ferric oxide and ferrosoferric oxide.

[0075] Preferably, the iron content in the iron powder is 95wt% or more, more preferably 99wt% or more, and even more preferably 99.5wt% or more, for example 99.7wt%.

[0076] Preferably, the iron powder is one or more of primary reduced iron powder, secondary reduced iron powder, carbonyl reduced iron powder and electrolytic iron powder.

[0077] Preferably, the purity of the ferric oxide is 95wt% or more, more preferably 99wt% or more, and even more preferably 99.5wt% or more.

[0078] Preferably, the purity of the ferrosoferric oxide is 95 wt % or more, more preferably 99 wt % or more, and even more preferably 99.5 wt % or more.

[0079] In step (2), the mesh size of the iron source is 100-1000 mesh, more preferably 200-500 mesh, for example 250 mesh or 300 mesh.

[0080] In step (2), the phosphoric acid solution generally refers to an aqueous phosphoric acid solution, and the mass percentage concentration of phosphoric acid in the phosphoric acid solution is preferably 20% to 85%, for example, 49%, 59% or 62%.

[0081] In step (2), the phosphoric acid in the phosphoric acid solution may be conventional phosphoric acid in the art, such as industrial grade phosphoric acid, food grade phosphoric acid, electrical grade phosphoric acid or electronic grade phosphoric acid, etc. The electrical grade phosphoric acid may be purchased from Guangxi Qinzhou Chengxing Chemical Technology Co., Ltd.

[0082] In step (2), the reaction temperature of the mixture of the iron source and the phosphoric acid solution is 20-95°C, more preferably 30-90°C, for example 35°C, 45°C, 55°C or 85°C.

[0083] In step (2), the mixture of the iron source and the phosphoric acid solution can be prepared by adding the iron source to the phosphoric acid solution under stirring.

[0084] In step (2), the molar ratio of the iron element provided by the iron source to the phosphorus element provided by the phosphoric acid is (0.94-1.05):1, more preferably (0.96-1.0):1, for example, 0.98:1 or 0.995:1.

[0085] In step (2), the mixture of the iron source and the phosphoric acid solution may further include a catalyst. The catalyst has a catalytic effect during the reaction and can be used as a doping element to improve the conductivity of the lithium iron phosphate product after the reaction.

[0086] The catalyst is preferably a titanium-based catalyst, such as titanium dioxide, and the molar ratio of the titanium element provided by the titanium-based catalyst to the phosphorus element provided by the phosphoric acid is preferably (0.01-0.02):1, such as 0.0145:1.

[0087] Wherein, the added amount of the catalyst is preferably 0.5wt%~2wt% of the added amount of the iron source.

[0088] The catalyst is preferably added by first mixing the catalyst with the phosphoric acid solution and then adding the iron source.

[0089] In step (2), the grinding operation and conditions can be conventional grinding operations, such as sand milling or ball milling.

[0090] Preferably, the grinding is performed using a sand mill. The sand mill is preferably a vertical sand mill, a horizontal sand mill (e.g., a nano-scale horizontal sand mill), a basket sand mill, or a double-cone rod sand mill. The particle size of the grinding beads used in the sand mill is preferably 0.1 to 3.0 mm, for example, 0.3 mm or 0.4 mm. The grinding beads used in the sand mill are preferably zirconia beads.

[0091] In step (2), the viscosity of the product A is 8000-20000 cps, more preferably 10000-20000 cps, for example 15000 cps.

[0092] In step (2), the organic acid solution generally refers to an aqueous solution of an organic acid, and the mass percentage concentration of the organic acid in the organic acid solution is 5% to 98%, preferably 55%, 62% or 72%.

[0093] In step (2), the organic acid in the organic acid solution is one or more of a carboxylic acid compound, ascorbic acid, and a polymer obtained by free radical polymerization of an unsaturated olefin containing a carboxylic acid.

[0094] The carboxylic acid compound is preferably one or more of formic acid, acetic acid, oxalic acid, citric acid, tartaric acid and malic acid.

[0095] The high molecular polymer is preferably polyacrylic acid and / or polymethacrylic acid.

[0096] The organic acid is, for example, malic acid, a "mixture of citric acid and oxalic acid" or a "mixture of malic acid and tartaric acid".

[0097] In step (2), the amount of the organic acid solution added may be 15 wt % to 60 wt %, for example 17 wt %, where the percentage is the mass of the organic acid in the organic acid solution relative to the mass of the phosphoric acid.

[0098] In step (2), the lithium source may be a lithium-containing compound conventionally used in the art, preferably one or more of lithium hydroxide monohydrate, lithium carbonate, lithium dihydrogen phosphate, lithium phosphate and lithium acetate, more preferably lithium hydroxide monohydrate and / or lithium acetate; the lithium carbonate is preferably industrial grade lithium carbonate or battery grade lithium carbonate.

[0099] In step (2), the molar ratio of the lithium element in the lithium source to the phosphoric acid in the phosphoric acid solution may be (0.98-1.05):1, for example, 1.02:1, 1.03:1 or 1.04:1.

[0100] In step (2), the carbon source may be one or more of carbon materials, metal compounds and conductive polymers;

[0101] When the carbon source is a carbon material, the carbon material may be glucose, a glucose derivative, a carboxylic acid, a carboxylic acid derivative, a phenolic resin, polyethylene, polyethylene glycol, polyvinyl alcohol, a polyvinyl alcohol derivative, polyacrylic acid, a polyacrylic acid derivative, a heterocyclic polymer or a condensation polymer with N or O elements; the glucose derivative preferably includes at least one of glucose, sucrose, starch and cyclodextrin; the carboxylic acid preferably includes at least one of formic acid, acetic acid, oxalic acid, citric acid, tartaric acid and malic acid; the polyacrylic acid derivative preferably includes polyacrylate; the heterocyclic polymer with N or O elements preferably includes polyvinyl pyrrolidone.

[0102] When the carbon source is a metal compound, the metal compound includes aluminum oxide and / or zinc stannate.

[0103] When the carbon source is a conductive polymer, the conductive polymer includes one or more of polyaniline, polystyrene thiol, polyacetylene, lithium carbonate and polycarbonate.

[0104] In some embodiments, the carbon source is lithium carbonate and sucrose.

[0105] In some embodiments, the carbon source is citric acid and polyacrylic acid.

[0106] In some embodiments, the carbon source is lithium carbonate, sucrose and polyvinyl pyrrolidone.

[0107] In some embodiments, the carbon source is a mixture of polyvinyl alcohol, cyclodextrin and polyethylene glycol.

[0108] In step (2), the amount of the carbon source added is 5 wt% to 25 wt% of the phosphoric acid, for example, 9.5 wt%.

[0109] In step (2), the reaction temperature of the mixture of the organic acid solution, the lithium source and the carbon source is 20-95°C, more preferably 30-90°C, for example 35°C, 40°C, 45°C or 55°C.

[0110] In step (2), the mixture of the organic acid solution, the lithium source and the carbon source is prepared by adding the lithium source and the carbon source into the organic acid solution under stirring.

[0111] In step (2), the mixture of the product A and the product B is generally prepared by mixing the product A and the product B.

[0112] In step (2), the grinding operation and conditions may be conventional in the art. The preferred implementation of the grinding may be the same as S1.

[0113] In step (2), the grinding time can be conventional in the art and will be affected by factors such as the size of the zirconium beads, the feed rate, and the wear of the zirconium beads. Specifically, the average particle size of the slurry is controlled, and the sanding is stopped when the sanding reaches the target particle size. The corresponding time is not fixed, for example, 6 to 10 hours.

[0114] In step (2), the lithium iron phosphate precursor may also be spray dried.

[0115] Wherein, during the spray drying, the air inlet temperature can be 280°C.

[0116] Wherein, during the spray drying, the outlet temperature can be 130°C.

[0117] In step (2), the average particle size of the lithium iron phosphate precursor may be 50 nm to 800 nm, for example, 200 nm.

[0118] In step (3), the solid content of the mixture may be 20 wt% to 80 wt%, preferably 30 wt% to 60 wt%, for example 35 wt%.

[0119] In step (3), the particle size of the particles in the ground slurry may be 200 nm to 2000 nm, for example. Grinding can fully mix the lithium iron phosphate precursor and lithium iron manganese phosphate, which is conducive to forming a uniform lithium iron phosphate coating layer.

[0120] In step (3), after grinding and before sintering, the mixture is generally dried. The drying method can be spray drying. The temperature parameters of the spray drying are preferably: air inlet temperature: 220°C, outlet temperature: 110°C.

[0121] In step (3), the sintering temperature may be 680°C to 750°C.

[0122] In some specific embodiments, in step (3), the sintering temperature is 650°C, 700°C, 730°C or 750°C.

[0123] In step (3), the sintering time can be 5h~20h.

[0124] In step (3), the heating rate of the sintering may be 3-10°C / min, for example 5°C / min.

[0125] In step (3), the sintering can be performed under an inert atmosphere, and the inert atmosphere is preferably a nitrogen atmosphere with a purity of 99.999%.

[0126] In step (3), the crushing method can be air flow crushing, and the manganese iron phosphate lithium composite material with a D50 particle size of 0.8 μm to 1.8 μm is obtained by crushing.

[0127] The present invention also provides a lithium manganese iron phosphate composite material, which is prepared by the preparation method as described above.

[0128] In the present invention, the average particle size of the lithium manganese iron phosphate core is 700nm~1000nm.

[0129] In some specific embodiments, the average particle size of the lithium manganese iron phosphate core is 600nm, 800nm ​​or 1200nm.

[0130] In the present invention, a first carbon layer may be further included between the lithium iron phosphate core and the lithium iron phosphate coating layer; the thickness of the first carbon layer is preferably 0 nm to 5 nm. A thicker first carbon layer is not conducive to ion conduction. When the lithium iron manganese phosphate is sintered in a reducing atmosphere such as hydrogen and no carbon remains, the thickness of the carbon layer is 0 nm.

[0131] In some specific embodiments, the thickness of the first carbon layer is 2 nm or 3 nm.

[0132] In the present invention, the carbon content of the lithium manganese iron phosphate composite material is 0.3% to 1.5%, where the percentage is the mass of the carbon element as a percentage of the total mass of the lithium manganese iron phosphate composite material. A low carbon content cannot provide an effective reducing atmosphere, resulting in the prepared lithium manganese iron phosphate composite material having no electrochemical activity.

[0133] In some specific embodiments, the carbon content of the lithium manganese iron phosphate composite material is 1.02%, 1.24%, 1.28%, 1.29%, 1.3%, 1.31%, 1.33%, 1.34%, 1.36%, 1.37%, 1.39%, 1.41% or 1.42%.

[0134] In the present invention, the thickness of the lithium iron phosphate coating layer is 2nm~30nm, for example, 3nm, 4nm or 5nm.

[0135] In the present invention, the thickness of the carbon coating layer may be 2 nm to 5 nm, for example, 3 nm, 4 nm or 5 nm.

[0136] In the present invention, the molar ratio of manganese element to iron element in the manganese iron phosphate lithium composite material can be (5-9): (5-1), such as 5:5, 6:4, 7:3 or 8:2. Within this range, the manganese iron phosphate lithium composite material can achieve better comprehensive performance, that is, the energy density and the Jan-Taylor effect reach a balanced value.

[0137] In the present invention, the D50 particle size of the lithium iron manganese phosphate composite material can be 0.8μm~1.8μm, for example, 1.17μm, 1.18μm, 1.2μm, 1.21μm, 1.22μm, 1.23μm, 1.24μm, 1.26μm, 1.27μm, 1.28μm, 1.29μm, 1.31μm, 1.42μm, 1.43μm or 1.45μm.

[0138] The present invention also provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes the lithium manganese iron phosphate composite material as described above.

[0139] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0140] The reagents and raw materials used in the present invention are commercially available.

[0141] The positive and progressive effects of the present invention are:

[0142] The lithium iron phosphate coating layer in the lithium iron manganese phosphate composite material provided by the present invention can effectively alleviate the dissolution of manganese ions in the lithium iron manganese phosphate. At the same time, the lithium iron phosphate coating layer and the lithium iron manganese phosphate have similar structures, which avoids the occurrence of cracks in the material caused by problems such as inconsistent volume shrinkage of different coating layers during use, and is beneficial to improving the cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0143] Figure 1This is a schematic diagram of the structure of the lithium iron manganese phosphate composite material obtained in Example 1. (1-lithium iron manganese phosphate core; 2-first carbon layer; 3-lithium iron phosphate coating layer; 4-carbon coating layer)

[0144] Figure 2 This is a TEM image of the lithium manganese iron phosphate composite material prepared in Example 1.

[0145] Figure 3 This is a TEM image of the lithium iron phosphate coated lithium manganese iron phosphate of the lithium iron phosphate composite material prepared in Example 1. DETAILED DESCRIPTION

[0146] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0147] Example 1

[0148] (1) Preparation of lithium manganese iron phosphate core

[0149] S1. Add iron powder and manganese powder in a molar ratio of 6:4 to deionized water and stir to form reactant I; the solid content of reactant I is 65%; add a 20wt% malic acid solution to an 85wt% phosphoric acid solution and stir to form reactant II; wherein the amount of malic acid added is 24wt%, and the percentage is the mass of malic acid to the mass of phosphoric acid; the molar ratio of manganese to phosphorus is 0.6:1; the molar ratio of iron to phosphorus is 0.4:1;

[0150] Then, under nitrogen protection, reactant I was added dropwise to reactant II within 10 minutes, and stirring was performed while dropping. The nitrogen flow rate was set to 15 L / min, and the stirring speed was set to 500 rpm. The stirring speed could be adjusted according to the state of the solution to prevent the solution from splashing. The reaction was carried out at 85° C. for 5.5 hours to obtain a solution containing a ferromanganese phosphate precursor. The average particle size of the ferromanganese phosphate precursor was 1400 nm. The solid content of the ferromanganese phosphate precursor was 45%, the pH of the solution was 5.87, and the viscosity of the solution was 8000 mPa·s.

[0151] S2. Add lithium carbonate and titanium dioxide to deionized water, stir the reaction until no bubbles are generated, and obtain reactant III; the solid content of reactant III is 20wt%; the molar ratio of lithium element in lithium carbonate to phosphorus element in phosphoric acid in step S1 is 1.04:1; the molar ratio of titanium element in titanium dioxide to phosphorus element provided by phosphoric acid is 0.0145:1;

[0152] S3. Add the solution containing the manganese iron phosphate precursor obtained in the above step S1 to the reactant III at 60°C within 30 minutes, and add magnesium oxide while stirring. Control the solution temperature to 60°C. After stirring for 2 hours, start the sand mill for sand grinding to obtain a manganese iron phosphate lithium precursor slurry; the molar ratio of the magnesium element in the magnesium oxide to the phosphorus element provided by the phosphoric acid is 0.02:1.

[0153] S4. The above-mentioned lithium iron manganese phosphate precursor slurry is sequentially ground, dried, sintered and crushed to obtain lithium iron manganese phosphate; wherein, the drying conditions are: spray drying, the air inlet temperature is 220°C, and the air outlet temperature is 110°C. The sintering conditions are: in a nitrogen atmosphere with a purity of 99.999%, the temperature is gradually increased from room temperature to 450°C at a heating rate of 5°C / min, and the temperature is cooled at a constant temperature of 450°C for 5 hours to obtain a sintered product. The sintered product is treated with an air flow crushing device to obtain a lithium iron manganese phosphate core. The average particle size of the lithium iron manganese phosphate core is 800nm.

[0154] (2) Preparation of lithium iron phosphate precursor

[0155] S1. A phosphoric acid solution with a concentration of 62% and titanium dioxide are mixed, and then reduced iron powder (the iron content in the iron powder is 99.7wt%) is added, and the mixture is stirred at 85°C to react. Gas is generated during the reaction, and then the material is put into a sand mill for sand grinding. The grinding beads in the sand mill are 0.3mm zirconium oxide beads to obtain product A; wherein the molar ratio of iron element to phosphorus element in phosphoric acid is 0.995:1; the molar ratio of titanium element in titanium dioxide to phosphorus element provided by phosphoric acid is 0.0145:1; the above reaction is carried out under stirring, and the stirring speed is 30Hz; the viscosity of the obtained product A is 15000cps;

[0156] S2. A 15wt% malic acid solution, lithium carbonate and sucrose are mixed and reacted at 55°C until no gas is generated to obtain a product B; wherein the molar ratio of lithium element to phosphorus element of phosphoric acid is 1.04:1; the mass of sucrose is 9.5%, and the percentage is the mass of sucrose to the mass of phosphoric acid; the amount of malic acid added is 17wt%, and the percentage is the mass of malic acid to the mass of phosphoric acid;

[0157] S3. Add the mixture of product A and product B into a sand mill for sand grinding, wherein the grinding beads in the sand mill are 0.3 mm zirconium oxide beads, to obtain a lithium iron phosphate precursor, wherein the particle size of the lithium iron phosphate precursor is 200 nm.

[0158] (3) Preparation of lithium manganese iron phosphate composite material with a manganese iron ratio of 5:5

[0159] The lithium iron phosphate precursor obtained in step (2), the lithium manganese iron phosphate obtained in step (1) and water are mixed (the solid content of the mixture is 35 wt%) and sand-milled, dried, sintered and crushed to form a lithium manganese iron phosphate composite material. The molar ratio of manganese element and iron element in the lithium manganese iron phosphate to the iron element in the lithium iron phosphate precursor is 6:4:2; the particle size of the slurry after sand-milling is 600nm, and the drying conditions are: spray drying, the air inlet temperature is 220℃, and the air outlet temperature is 110℃. The sintering conditions are: in a nitrogen atmosphere with a purity of 99.999%, gradually heating from room temperature to 730℃ at a heating rate of 5℃ / min, keeping the temperature at 730℃ for 10h, and cooling to obtain a sintered product. The crushing method is: air flow crushing.

[0160] Example 2

[0161] The only difference from Example 1 is that the average particle size of the lithium manganese iron phosphate prepared in step (1) is 600 nm.

[0162] Example 3

[0163] The only difference from Example 1 is that the average particle size of the lithium manganese iron phosphate prepared in step (1) is 1200 nm.

[0164] Example 4

[0165] The only difference from Example 1 is that the molar ratio of the manganese element to the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor in step (3) is 7:3:4.

[0166] Example 5

[0167] The only difference from Example 1 is that the molar ratio of the manganese element to the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor in step (3) is 8:2:6.

[0168] Example 6

[0169] The only difference from Example 1 is that the molar ratio of the manganese element to the iron element in the lithium manganese iron phosphate in step (3) to the iron element in the lithium iron phosphate precursor is 9:1:8.

[0170] Example 7

[0171] The only difference from Example 1 is that the molar ratio of the manganese element to the iron element in the lithium manganese iron phosphate and the iron element in the lithium iron phosphate precursor in step (3) is 10:0:10.

[0172] Example 8

[0173] The only difference from Example 1 is that the molar ratio of manganese to iron in the lithium manganese iron phosphate composite material is 6:4, and the molar ratio of manganese to iron in the lithium manganese iron phosphate to the iron in the lithium iron phosphate precursor in step (3) is 7:3:1.7.

[0174] Example 9

[0175] The only difference from Example 1 is that the molar ratio of manganese to iron in the lithium manganese iron phosphate composite material is 9:1, and the molar ratio of manganese to iron in the lithium manganese iron phosphate and the iron in the lithium iron phosphate precursor in step (3) is 9.5:0.5:0.6.

[0176] Example 10

[0177] The only difference from Example 1 is that the sintering temperature in step (3) is 650°C.

[0178] Embodiment 11

[0179] The only difference from Example 1 is that the sintering temperature in step (3) is 700°C.

[0180] Example 12

[0181] The only difference from Example 1 is that the sintering temperature in step (3) is 750°C.

[0182] Example 13

[0183] The only difference from Example 1 is that the sintering temperature in step (1) is 680°C.

[0184] Embodiment 14

[0185] The only difference from Example 1 is that the sintering temperature in step (1) is 300°C.

[0186] Embodiment 15

[0187] The only difference from Example 1 is that malic acid is not added in step (1), and the sintering is carried out in a reducing gas, wherein the reducing gas is a mixture of nitrogen and hydrogen, with the volume proportion of hydrogen being 20%.

[0188] Example 16

[0189] The only difference from Example 1 is that titanium dioxide is not added in step (2).

[0190] Embodiment 17

[0191] The only difference from Example 1 is that titanium dioxide is not added in step (1).

[0192] Embodiment 18

[0193] The only difference from Example 1 is that magnesium oxide is not added in step (1).

[0194] Comparative Example 1

[0195] The only difference from Example 1 is that the average particle size of the lithium manganese iron phosphate prepared in step (1) is 400 nm.

[0196] Comparative Example 2

[0197] The only difference from Example 1 is that the average particle size of the lithium manganese iron phosphate prepared in step (1) is 1400 nm.

[0198] Comparative Example 3

[0199] The only difference from Example 1 is that the sintering temperature in step (3) is 600°C.

[0200] Comparative Example 4

[0201] The only difference from Example 1 is that the sintering temperature in step (3) is 800°C.

[0202] Comparative Example 5

[0203] The only difference from Example 1 is that the sintering temperature in step (1) is 720°C.

[0204] Comparative Example 6

[0205] The only difference from Example 1 is that the sintering temperature in step (1) is 250°C.

[0206] Effect Example 1 Physical and Chemical Properties of Lithium Manganese Iron Phosphate Composite Materials

[0207] (1) Thickness

[0208] A transmission electron microscope (manufacturer and model: JEOL 2100f, JOEL Ltd., Tokyo, Japan) was used to characterize the microstructure of the material, and its thickness was measured by software.

[0209] (2) Particle size

[0210] The particle size was tested using a laser particle size analyzer with a refractive index of 1.8%. The equipment model was Malvern 3000. The test results are shown in Table 1.

[0211] (3) Carbon content

[0212] Refer to the national standard: GBT 223.86-2009 Determination of total carbon content of steel and alloys - infrared absorption method after induction furnace combustion. (Equipment manufacturer, Keguo Instrument, model: HCS-500), the test results are shown in Table 1.

[0213] (4) Resistivity

[0214] The resistivity of the lithium manganese iron phosphate composite materials obtained in all the embodiments and comparative examples was tested using a powder resistivity tester (model: ST2742B). The test method was a four-probe test, the test pressure was 8 MPa, and the test results are shown in Table 1.

[0215] (5) Powder compaction density

[0216] The compaction density of lithium iron phosphate powder was tested by an electronic pressure testing machine (model UTM7305Z09). The pressure parameters were 10 kN, 20 kN and 30 kN. The compaction density of the powder under a pressure of 30 kN was taken as the test result. The test results are shown in Table 1.

[0217] (6) Specific surface area

[0218] Refer to the national standard: GB / T 33822-2017 to test the specific surface area per unit mass, the degassing temperature is 220℃, and the degassing time is 1h. (Equipment manufacturer, Beijing Jingwei Gaobo, model: JW-TB400), the test results are shown in Table 1.

[0219] (7) Manganese dissolution and iron dissolution

[0220] The lithium manganese iron phosphate composite materials prepared in the examples and comparative examples were vacuum dried at 105° C. for 2 h, 5 g of the pretreated sample was weighed, added to 100 ml of a 0.010 mol / L hydrochloric acid solution, stirred at room temperature for 20 min, and filtered to obtain a supernatant after standing for 2 h using a magnetic stirrer at a speed of 250 rpm. The supernatant was taken and the iron and manganese contents in the supernatant were tested (equipment manufacturer: Thermo Fisher Scientific China Co., Ltd., model: ICAP PRO XP).

[0221] Table 1

[0222]

[0223] Effect Example 2 Electrical properties of lithium manganese iron phosphate composite material

[0224] Button battery assembly

[0225] (1) The lithium manganese iron phosphate composite material, conductive carbon black and polyvinylidene fluoride of the embodiment and comparative example were dispersed in NMP solution at a mass ratio of 90:5:5, and stirred in a vacuum mixer for 3 hours, and the solid content of the slurry was controlled to be 50% to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on aluminum foil, and then placed in a vacuum drying oven at 120°C for 12 hours. After drying, it was punched into discs with a diameter of 12 mm as positive electrode sheets.

[0226] (2) A metal lithium sheet was used as the negative electrode, a Celgard 2400 microporous membrane was used as the separator, and a 1.0 mol / L LiPF6 solution was used as the electrolyte. The solvent of the electrolyte was prepared by mixing ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1. The positive electrode sheet, negative electrode sheet, separator and electrolyte were assembled into a CR2016 button cell in an argon-filled glove box.

[0227] The button cell prepared by the above method was used to test the electrical performance. During the test, the cut-off voltage of the charging process was 3.75V, and the cut-off voltage of the discharging process was 2.0V. Equipment manufacturer: Newwell Electronics Co., Ltd., equipment specification: 5V / 10mA.

[0228] (1) Discharge specific capacity

[0229] The button cell prepared by the above method was charged at a constant current of 0.1C to a voltage of 3.75V, then switched to constant voltage charging to a current of 0.02C, and discharged at a constant current of 0.1C to a voltage of 2.0V, and the 0.1C discharge specific capacity was recorded as the test result.

[0230] The button battery prepared by the above method was charged at a constant current of 1C to a voltage of 3.75V, then switched to constant voltage charging to a current of 0.02C, and discharged at a constant current of 1C to a voltage of 2.0V, and the 1C discharge specific capacity was recorded as the test result.

[0231] The test results are shown in Table 2.

[0232] (2) Cycle performance

[0233] The button cell prepared by the above method was charged and discharged at a rate of 1C in the charge and discharge range of 2.5V to 4.5V at 25°C using a charge and discharge machine (Blue Electric CT2001A). The cycle test was terminated when the capacity decayed to 80% of the initial capacity, and the number of cycles was recorded. The test results are shown in Table 2.

[0234] Table 2

[0235]

[0236] It can be seen from the data in Table 1 and Table 2 that the lithium manganese iron phosphate composite material provided by the present invention has the advantages of low resistivity and high compaction density. At the same time, according to the low iron dissolution and manganese dissolution, it can be seen that the lithium manganese iron phosphate composite material has a high degree of coating, which can effectively prevent the dissolution of manganese and iron, and has good electrical properties when applied to batteries. Taking the lithium manganese iron phosphate composite material with a manganese iron ratio of 5:5 as an example, when it is applied to a battery, the battery's 0.1C discharge capacity is 137.2mAh / g or more, 1C discharge capacity is 124.5mAh / g and above, and the number of cycles to 80% SOC under 1C conditions is 649 or more.

[0237] Figure 1 The schematic diagram is a structural diagram of the lithium iron manganese phosphate composite material prepared in Example 1. The composite material comprises a lithium iron manganese phosphate core, a first carbon layer, a lithium iron phosphate coating layer and a carbon coating layer. Figure 2 and Figure 3 TEM image of the lithium manganese iron phosphate composite material of Example 1. Figure 2 It can be seen that the outermost layer of the lithium manganese iron phosphate composite material has a complete carbon coating layer, indicating that its coating degree is good. Figure 3 It can be seen that there is a lithium iron phosphate coating layer on the surface of the lithium manganese iron phosphate core.

[0238] Examples 1-3 and Comparative Examples 1-2 verify various properties of lithium manganese iron phosphate composite materials with different lithium manganese iron phosphate core diameters. It can be seen that a lithium manganese iron phosphate core diameter that is too large or too small will affect the electrical properties.

[0239] The difference between Examples 1, 10-12 and Comparative Examples 3-4 is that the sintering temperatures in step (3) are different. The sintering temperature will affect the fusion and coating degree of the particles, thereby affecting the electrical properties of the material during application. When the temperature is too high or too low, a good coating structure cannot be formed.

[0240] The difference between Examples 1, 13-14 and Comparative Examples 5-6 is that the sintering temperatures in step (1) are different. According to the effect data of their cycle performance, the discharge specific capacity and cycle performance are significantly different. This may be because the sintering temperature affects the structure of the lithium manganese iron phosphate core. When the sintering temperature is too high or too low, the formed core is not conducive to subsequent coating.

[0241] Examples 1, 4-7 verify that different schemes can produce lithium iron manganese phosphate composite materials with a manganese iron ratio of 5:5 and good electrical properties. Examples 1, 8 and 9 verify that the scheme of the present invention can achieve the preparation of lithium iron manganese phosphate composite materials with different manganese iron ratios.

[0242] The above-described embodiments are only preferred embodiments of the present invention, which are convenient for those skilled in the art to understand and use the present invention. Obviously, any person skilled in the art can slightly modify or change the present embodiment and apply it to other embodiments without creative work. Therefore, the present invention is not limited to the above-described embodiments, and any equal changes, simple modifications and modifications made within the scope of the present invention still belong to the scope of the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate composite material, characterized in that: It includes the following steps: (1) reacting reactant I with reactant II to obtain a ferromanganese phosphate precursor; reactant I includes an iron source, a manganese source and water; reactant II includes a phosphorus source, a first organic acid and water; then reacting the ferromanganese phosphate precursor with reactant III to obtain a lithium iron manganese phosphate precursor, and then grinding, sintering and crushing in sequence to obtain the lithium iron manganese phosphate; reactant III includes a lithium source and water; the sintering temperature is 300° C. to 680° C.; (2) reacting a mixture of an iron source and a phosphoric acid solution, and grinding the mixture after the reaction is completed to obtain a product A; reacting a mixture of an organic acid solution, a lithium source, and a carbon source, and obtaining a product B after the reaction is completed; the order of preparing the product A and the product B is not limited; grinding the mixture of the product A and the product B to obtain a lithium iron phosphate precursor; (3) Grinding, sintering and crushing a mixture including the lithium iron phosphate, the lithium iron phosphate precursor and water to form the lithium iron phosphate composite material; the sintering temperature is 650°C to 750°C; wherein the lithium iron phosphate forms the inner core of the lithium iron phosphate composite material, and the average particle size of the inner core is 600nm to 1200nm; the lithium iron phosphate precursor forms the lithium iron phosphate coating layer and the carbon coating layer of the lithium iron phosphate composite material.

2. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: The preparation method of the lithium iron manganese phosphate composite material meets one or more of the following conditions ae: a. The molar ratio of the manganese element, the iron element and the iron element of the lithium iron phosphate precursor is (1-x):x:y, wherein (1-x):(x+y)=(5-9):(5-1); b. In step (1), the sintering temperature is 400°C to 500°C; c. In step (1), the average particle size of the lithium manganese iron phosphate is 700nm to 1000nm; d. In step (2), the average particle size of the lithium iron phosphate precursor is 50nm to 800nm; e. In step (3), the sintering temperature is 680°C to 750°C.

3. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: Step (3) of the method for preparing the lithium manganese iron phosphate composite material satisfies one or more of the following conditions ae: a. The particle size of the particles in the ground slurry is 200nm to 2000nm; b. The solid content of the mixture is 20wt% to 80wt%; c. The sintering time is 5h to 20h; d. The sintering is carried out under an inert atmosphere, wherein the inert atmosphere is a nitrogen atmosphere with a purity of 99.999%; e. After the grinding and before the sintering, the mixture is dried by spray drying.

4. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: Step (1) of the method for preparing the lithium manganese iron phosphate composite material satisfies one or more of the following conditions a1: a. The iron source is at least one of iron powder, ferroferric oxide, ferric oxide and iron oxide; b. The manganese source is at least one of manganese powder, manganese trioxide, manganese tetraoxide, manganese oxide, and manganese carbonate; c. the manganese source and the iron source are added in the form of ferromanganese alloy; d. The lithium source is at least one of lithium carbonate and lithium hydroxide; e. The molar ratio of the iron element provided by the iron source to the phosphorus element provided by the phosphorus source is (0.35 to 0.15): 1; f. The molar ratio of the manganese element provided by the manganese source to the phosphorus element provided by the phosphorus source is (0.4 to 1.0): 1; g. The molar ratio of the lithium element provided by the lithium source to the phosphorus element provided by the phosphorus source is (1.01 to 1.05): 1; h. adding a first organic acid to at least one of the reactants II and III, wherein the first organic acid is at least one of a monocarboxylic acid, a dicarboxylic acid and a tricarboxylic acid; the amount of the first organic acid added is 15wt% to 60wt%, where the percentage is the mass of the first organic acid to the mass of the phosphoric acid; i. At least one of the reactants I and III further comprises a first dopant, wherein the first dopant comprises at least one of magnesium, cobalt, titanium, vanadium, nickel, niobium, copper and tungsten; the molar ratio of the doping element provided by the first dopant to the phosphorus element provided by the phosphorus source is (0.01-0.05):1; j. The reactant III further comprises a reducing substance, wherein the reducing substance is one or more of a carbon material and a conductive polymer; When the reducing substance is a carbon material, the carbon material is glucose, a glucose derivative, a carboxylic acid, a carboxylic acid derivative, a phenolic resin, polyethylene, polyethylene glycol, polyvinyl alcohol, a polyvinyl alcohol derivative, polyacrylic acid, a polyacrylic acid derivative, a heterocyclic polymer or a condensation polymer with N or O elements; the glucose derivative includes at least one of glucose, sucrose, starch and cyclodextrin; the carboxylic acid includes at least one of formic acid, acetic acid, oxalic acid, citric acid, tartaric acid and malic acid; the polyacrylic acid derivative includes polyacrylate; the heterocyclic polymer with N or O elements includes polyvinyl pyrrolidone; When the reducing substance is a conductive polymer, the conductive polymer includes one or more of polyaniline, polystyrene thiol, polyacetylene, lithium carbonate and polycarbonate; k. The sintering time is 5h to 20h; 1. The sintering is carried out in a reducing gas, which is a mixed gas of nitrogen and hydrogen or a mixed gas of argon and hydrogen; the volume of hydrogen in the reducing gas accounts for 20%.

5. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: Step (2) of the method for preparing the lithium manganese iron phosphate composite material satisfies one or more of the following conditions ai: a. The iron source is one or more of iron powder, ferric oxide, ferrosoferric oxide and ferric nitrate; b. The organic acid in the organic acid solution is one or more polymers obtained by copolymerizing carboxylic acid compounds, ascorbic acid and unsaturated olefins containing carboxylic acids through free radical polymerization; When the organic acid is a carboxylic acid compound, the carboxylic acid compound is one or more of formic acid, acetic acid, oxalic acid, citric acid, tartaric acid and malic acid; When the organic acid is a high molecular polymer, the high molecular polymer is polyacrylic acid and / or polymethacrylic acid; c. The lithium source is one or more of lithium hydroxide monohydrate, lithium carbonate, lithium dihydrogen phosphate, lithium phosphate and lithium acetate; d. The carbon source is one or more of a carbon material and a conductive polymer; e. The molar ratio of the iron element provided by the iron source to the phosphorus element provided by the phosphoric acid is (0.94 to 1.05): 1; f. The amount of the organic acid solution added is 15wt% to 60wt%, where the percentage is the mass of the organic acid in the organic acid solution as a percentage of the mass of the phosphoric acid; g. The molar ratio of the lithium element in the lithium source to the phosphoric acid in the phosphoric acid solution is (0.98 to 1.05): 1; h. The amount of the carbon source added is 5% to 25% by mass of the phosphoric acid; i. The mixture of the iron source and the phosphoric acid solution also includes a titanium catalyst, and the molar ratio of the titanium element provided by the titanium catalyst to the phosphoric acid is (0.01-0.02):

1.

6. The method for preparing the lithium iron manganese phosphate composite material according to claim 5, characterized in that: The carbon source is a carbon material, and the carbon material is glucose, glucose derivatives, carboxylic acids, carboxylic acid derivatives, phenolic resin, polyethylene, polyethylene glycol, polyvinyl alcohol, polyvinyl alcohol derivatives, polyacrylic acid, polyacrylic acid derivatives, heterocyclic polymers or polycondensates with N or O elements; the glucose derivatives include at least one of glucose, sucrose, starch and cyclodextrin; the carboxylic acids include at least one of formic acid, acetic acid, oxalic acid, citric acid, tartaric acid and malic acid; the polyacrylic acid derivatives include polyacrylates; the heterocyclic polymers with N or O elements include polyvinyl pyrrolidone; And / or, the carbon source is a conductive polymer, and the conductive polymer includes one or more of polyaniline, polystyrene thiol, polyacetylene, lithium carbonate and polycarbonate.

7. A lithium manganese iron phosphate composite material, characterized in that: The composite material is prepared by the method for preparing the lithium manganese iron phosphate composite material as claimed in any one of claims 1 to 6.

8. The lithium iron manganese phosphate composite material according to claim 7, characterized in that: The lithium iron manganese phosphate composite material satisfies one or more of the following conditions ac: a. The thickness of the lithium iron phosphate coating layer is 2nm to 30nm; b. The thickness of the carbon coating layer is 2nm to 5nm; c. A first carbon layer is further included between the lithium manganese iron phosphate core and the lithium iron phosphate coating layer, and the thickness of the first carbon layer is 0 nm to 5 nm.

9. The lithium iron manganese phosphate composite material according to claim 7, characterized in that: The lithium iron manganese phosphate composite material satisfies one or more of the following conditions ac: a. The carbon content of the lithium manganese iron phosphate composite material is 0.3% to 1.5%, where the percentage is the mass of the carbon element as a percentage of the total mass of the lithium manganese iron phosphate composite material; b. The molar ratio of manganese element to iron element in the lithium manganese iron phosphate composite material is (5 to 9): (5 to 1); c. The D50 particle size of the lithium manganese iron phosphate composite material is 0.8 μm to 1.8 μm.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet comprises a positive electrode active material. The positive electrode active material comprises the lithium manganese iron phosphate composite material according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Lithium manganese ferric phosphate (LMFP) material with core-cell structure as well as preparation method and application thereof

    CN106299296A

  • Single-core multi-shell lithium manganese iron phosphate composite positive electrode material and preparation method thereof

    CN117832421A